Aplikasi Tik-Tok: Pengembangan Media Pembelajaran Matematika Materi Barisan dan Deret Untuk Meningkatkan Minat Belajar Siswa SMA - Vidyastuti, Annisa Nurina; Effendi, Mohammad Mahfud; Darmayanti, Rani (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2022)
Learning media is an educational innovation that continues to grow. This is related to art learning, especially the making of learning media using the tik-tok application. This application is an innovation made for the purpose of expression, but in the context of tik-tok learning, it can be used as a digital space to take advantage of technological developments and make it freely accessible to students of SMA YALC Pasuruan. In this study, we used a qualitative description method. Tik-tok application-based learning activities are used in mathematics. This learning activity recognizes line and series content and loads it into a video with an audio track. By using the editing capabilities of each video content that functions as a learning medium, with an emphasis in the form of explanations that are understood audiovisually. With the development of this media technology, students will be able to learn independently by playing the tik-tok application and watching videos. In addition, as long as students use tik-tok social media, educators can monitor the learning process.